Analysis of Politeness Maxims in Indonesian Language Use in College Environments - Puspawati, Anita (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
Language politeness is part of pragmatics which studies the use of language in communication. Pragmatics examines context-bound meaning, in contrast to semantics which examines context-free meaning. In interaction, the ability to speak clearly and politely is essential for effective communication. Leech's Principles of Politeness include six maxims: tact, generosity, approbation, modesty, agreement, and sympathy maxim. This study aims to describe the realization of language politeness in the college environment based on Leech's six maxims of politeness. The method used is pragmatic analysis with a qualitative approach. Data were collected through observation and documentation of conversations in the campus environment of Bandung Islamic University (Unisba). Leech's theory is used because it is able to assess politeness from two perspectives, namely the speaker and the interlocutor. The results show that the principle of politeness is still often violated in campus communication. Therefore, the understanding and application of language politeness need to be improved in daily life and made part of learning in schools and universities so that academic and social communication is more effective and harmonious.